2009
DOI: 10.1021/nn900735y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CdSe Nanocrystal Diffraction Gratings Prepared by Microcontact Molding

Abstract: We describe the formation of efficient transmission diffraction gratings created from patterned high quality ligand-capped CdSe nanocrystals (NCs), using a facile microcontact molding procedure. Soft polymer replicas of commercially available master gratings were "inked" with solvated NCs and the resulting pattern transferred to a variety of substrates after drying. Large-area (>0.5 cm(2)), defect free diffraction gratings were prepared with a variety of submicrometer line spacings and feature sizes down to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Even though the identical stamp is used for all gratings, we find that the reproducibility of the stamping is not perfect, leading to slightly different grating periods ( Λ = 416.4 … 433.2 nm) and modulation depths defined as peak‐to‐valley distance ( M = 95.3 … 127.5 nm) between stampings. The observed concentration‐dependent morphology of the 1D truncated half‐sine‐like nanocrystal structures is consistent with those seen in the original report by Armstrong et al when sinusoidal PDMS replicas (produced from holographic master gratings) are used . The gratings in type B devices exhibit a sinusoidal profile with peak‐to‐valley modulation depth of M ≈ 60 nm (see Figure S7).…”
Section: Device and Lasing Properties Of Type A With Y‐nc Gratings Ansupporting
confidence: 88%
See 2 more Smart Citations
“…Even though the identical stamp is used for all gratings, we find that the reproducibility of the stamping is not perfect, leading to slightly different grating periods ( Λ = 416.4 … 433.2 nm) and modulation depths defined as peak‐to‐valley distance ( M = 95.3 … 127.5 nm) between stampings. The observed concentration‐dependent morphology of the 1D truncated half‐sine‐like nanocrystal structures is consistent with those seen in the original report by Armstrong et al when sinusoidal PDMS replicas (produced from holographic master gratings) are used . The gratings in type B devices exhibit a sinusoidal profile with peak‐to‐valley modulation depth of M ≈ 60 nm (see Figure S7).…”
Section: Device and Lasing Properties Of Type A With Y‐nc Gratings Ansupporting
confidence: 88%
“…Incorporation of NCs into such devices relies on the ability to precisely control their morphology, either as pure materials or hybrid blends with organic polymers, on nanometer length scales to facilitate photoinduced (e.g., solar fuel and photovoltaic applications) and dark (e.g., field effect transistors and light‐emitting diodes) charge transfer. Directed lithographic self‐assembly of NCs on the nanoscale has also been employed to fabricate patterned features that can act as photonic structures (e.g., gratings or lasers), nanoelectronic circuits and sensors . All the aforementioned applications rely on controlling the interaction of the ligand‐capped NCs with a variety of materials and substrates to afford the desired nanoscale morphology (i.e., nanoscale phase separation, crack‐free film formation and high‐fidelity nanoscale pattern replication for hybrid photovoltaics, nanocrystal solar cells/transistors and photonic structures/sensors, respectively).…”
Section: Device and Lasing Properties Of Type A With Y‐nc Gratings Anmentioning
confidence: 99%
See 1 more Smart Citation
“…These fundamental approaches can be easily combined to attain multi-color patterns from only one batch of QDs. The methods presented here are also compatible with other micro-fabrication technologies of QDs embossed emission patterns, such as stamp mold [19,20], e-beam lithography [21,22] and flow coating [23]. The combination of PA, LSPR and annealing undoubtedly provides an effective way of precisely tuning the colors of light-emitting materials and devices that use colloidal CdSe QDs.…”
Section: Discussionmentioning
confidence: 84%
“…Thomas et al first demonstrated this technique with a nanocrystal–titania prepolymer solution . Shallcross and co‐workers, have developed micromolding patterned gratings with both CdSe ink and a mixture of CdSe and a red‐emitting polymer . Though this method can be applied in mild conditions, generally the quality is not as good as nanoimprint, as the uniformity across large areas could not be easily obtained (Figure e).…”
Section: Molding Approachesmentioning
confidence: 99%